2019
DOI: 10.1002/aic.16830
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the effect of inclination angle on the minimum conveying velocity and the underlying mechanisms

Abstract: This work investigated the effect of inclination angle on the minimum conveying velocity and the underlying mechanisms. Results showed that the pressure drop increased first and then decreased with the increasing inclination angle at the same mass flux and superficial gas velocity. The changing trend of minimum conveying velocity (u min) and the pressure drop near it can be divided into two types by taking 45 as the boundary, which was consistent with the difference in flow regimes near u min at different incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The passive acoustic emission (AE) detection technology is just a monitoring method based on this. Because it has the characteristics of real‐time, on‐line and environmental‐friendly, the passive AE detection technology has been widely used in various chemical industries related to gas–liquid two‐phase flows, gas–solid two‐phase flows, as well as chemical reactions systems 1‐8 . Especially in gas–solid flows, the particle‐size distribution, 2,3 solid mass flow rate, 4 flow pattern 5 and fault diagnosis 6 have been measured or identified by collecting and analyzing the AE signals generated by particle movements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The passive acoustic emission (AE) detection technology is just a monitoring method based on this. Because it has the characteristics of real‐time, on‐line and environmental‐friendly, the passive AE detection technology has been widely used in various chemical industries related to gas–liquid two‐phase flows, gas–solid two‐phase flows, as well as chemical reactions systems 1‐8 . Especially in gas–solid flows, the particle‐size distribution, 2,3 solid mass flow rate, 4 flow pattern 5 and fault diagnosis 6 have been measured or identified by collecting and analyzing the AE signals generated by particle movements.…”
Section: Introductionmentioning
confidence: 99%
“…Because it has the characteristics of real-time, on-line and environmental-friendly, the passive AE detection technology has beenwidely used in various chemical industries related to gas-liquid twophase flows, gas-solid two-phase flows, as well as chemical reactions systems. [1][2][3][4][5][6][7][8] Especially in gas-solid flows, the particle-size distribution, 2,3 solid mass flow rate, 4 flow pattern 5 and fault diagnosis 6 have been measured or identified by collecting and analyzing the AE signals generated by particle movements. However, most of AE signals were only collected from the surface of measured devices, which were superimposed AE signals generated in the detection area of the sensor, and the signal-to-noise ratio was low.…”
mentioning
confidence: 99%
“…Recently, Sun et al defined the particle entrainment rate based on the original Kalman pickup velocity prediction model, and Zhou et al experimentally showed that this model was also appropriate for lump coal particle pickup and modified the zone I equation. Zhang et al investigated the effect of the inclination angle on the minimum conveying velocity and the underlying mechanisms. Other typical researchers, such as Anantharaman et al focused on the nanoscale particle pickup process and pickup velocity prediction and developed a prediction equation for Geldart B particles.…”
Section: Introductionmentioning
confidence: 99%